2021
DOI: 10.1038/s41467-021-27377-3
|View full text |Cite
|
Sign up to set email alerts
|

Diblock dialternating terpolymers by one-step/one-pot highly selective organocatalytic multimonomer polymerization

Abstract: The synthesis of well-defined block copolymers from a mixture of monomers without additional actions (“one-pot/one-step”) is an ideal and industrially valuable method. In addition, the presence of controlled alternating sequences in one or both blocks increases the structural diversity of polymeric materials, but, at the same time, the synthetic difficulty. Here we show that the “one-pot/one-step” ring-opening terpolymerization of a mixture of three monomers (N-sulfonyl aziridines; cyclic anhydrides and epoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 49 publications
1
46
0
Order By: Relevance
“…Recently, the ring-opening alternating copolymerisation (ROAC) of cyclic anhydrides and epoxides has attracted much attention as a third method to access polyesters following polycondensation and ROP because it affords more advantages than them. [22][23][24][25][26][27][28][29][30][31] Polyesters obtained by ROAC involve two types of monomers in the repeating unit, which allow for the easy construction of polymer libraries with a broad structural diversity. In addition, polyesters with functional side chains can be easily synthesised using epoxides having functional side chains.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the ring-opening alternating copolymerisation (ROAC) of cyclic anhydrides and epoxides has attracted much attention as a third method to access polyesters following polycondensation and ROP because it affords more advantages than them. [22][23][24][25][26][27][28][29][30][31] Polyesters obtained by ROAC involve two types of monomers in the repeating unit, which allow for the easy construction of polymer libraries with a broad structural diversity. In addition, polyesters with functional side chains can be easily synthesised using epoxides having functional side chains.…”
Section: Introductionmentioning
confidence: 99%
“…(ABC) n or (ABAC) n , are unknown. [42][43][44][45][46][47][48] The hypothesis of O/S exchange here led us to discover a new type of polymerisation, sequence selective ring-opening terpolymerisation (ROTERP) that we report in this contribution. ROTERP produces poly(ester-altester-alt-trithiocarbonates), i.e.…”
mentioning
confidence: 96%
“…Recently, Hadjichristidis et al reported a breakthrough finding of N-sulfonyl aziridines (Az)'s control over the copolymerization of epoxides in couple with PA (Figure 12). 112 With the t BuP 1 catalyst, perfect diblock copolymers were produced from a mixture of Az, PA, and epoxide monomers. The first-stage ROCOP of PA/Az proceeded very fast.…”
Section: ■ Control Over Epoxidesmentioning
confidence: 99%